Palliative radiotherapy in older adults with head and neck squamous cell carcinoma: A systematic review. (August 2021) - Desideri, I.; Becherini, C.; Belgioia, L.; Merlotti, A.; Ciccone, L.P.; Franzese, C.; Loi, M.; De Felice, F.; Mazzola, R.; Caini, S.; Livi, L.; Bonomo, P.
Highlights: Locally advanced SCCHN is a common oncologic pathology in older adults. It's unclear what is the optimal palliative radiation regimen for older adults SCCHN. The use and the role of quality of life and geriatric assessment are unexplored. Radiotherapy is an effective palliative treatment for symptomatic older adults SCCHN. Abstract: Locally advanced Head and neck squamous cell carcinoma (SCCHN) represents a common oncologic pathology in older adults (OA). While radiotherapy represents a cornerstone in this context, it is unclear what is the optimal radiation regimen for SCCHN in the palliative setting, especially for OA. This article addresses issues related to palliative radiotherapy (PRT) in this setting with a focus on treatment modalities and toxicity. We also explore the use of quality of life and geriatric assessment in this setting. Medline, Scopus and Embase databases were queried for articles in this setting. We included studies published from January 1, 2000 through June 1, 2020, that were independently evaluated by two authors. Analyzed endpoints were progression free survival (PFS), overall survival (OS) and PRT toxicities. The meta -analysis was performed using Stata v.14. A total of 33 studies were included in this meta -analysis. The pooled median OS is 7.7 months, 2-years OS was worse for higher radiation dose (p = 0.02). The pooled median PFS was 5.4 months, PFS was influenced by EQD2 (p = 0.01), with patients receiving an EQD2 < 40 Gy that presented a poorer outcome. Regarding acute toxicities, most common pooled G3 toxicities were mucositis (7%) and dysphagia (15%). Among late toxicity, most common G3 toxicity was dysphagia in 7% of patients. Radiotherapy should be the most effective palliative treatment in symptomatic SCCHN OA. A tailored approach, guided by geriatric tools, would be indicated to choose the right therapy.